Insight. Upper-Intermediate: teacher's book - Stannett K. Katherine (Oxford Exam Support)
Teacher's Book in-depth teaching notes with additional cultural and language information for full classroom support extra activities offer flexible alternatives - tailor the course to suit your class. answer keys and audio scripts. Teacher's Resource Disk DVD extra: documentary video clips linked to each unit plus ready-to-use DVD extra worksheets and teacher's notes: Communication worksheets for pair and group practice of key language from the Student's Book.